Assess Nurses' Social Media Conduct's Effect on Patient Trust - Zebidi , Nadia Ageel; Bajammal, Emtenan Abdulfattah; alshaikhi, Fatimah ahmed; Almeshal , Munirah Ali; albarnawi, Bashaer khedr; alghamdi , Azizah ali; Alnajim, Norah Abdullah; Albalawi , Hajar Saud; Hadadi , Ashjan Ali; Alotaibi , Dalal hamoud; Alghamdi , Abdrhman Ahmad Hassan; Al Zahrani, Saeed Mohammad Khorman (Journal of Ecohumanism, 2024)
Background: The increasing reliance on social media has transformed how healthcare professionals, including nurses, access and share medical knowledge. Digital platforms such as WhatsApp, Facebook, Twitter, and LinkedIn provide avenues for professional networking, information exchange, and patient education. However, challenges such as misinformation, privacy concerns, and ethical dilemmas complicate the use of these tools in clinical practice. This study explores the role of social media in nursing, examining its benefits, risks, and the types of health information sought by nurses. Methods: A mixed-method, cross-sectional study design was employed, integrating quantitative and qualitative approaches. Data were collected from 280 nurses through structured questionnaires and focus group discussions (FGDs). The survey assessed demographic characteristics, social media usage patterns, and perceptions of its advantages and challenges. Quantitative data were analyzed using SPSS, while qualitative insights were derived through thematic analysis using NVivo software. Results: Findings indicate that WhatsApp, Facebook, and Twitter are the most frequently used platforms for accessing health information. Nurses primarily sought information on patient experiences, health conditions, and second opinions, while topics such as insurance, medication, and therapy details received less attention. Key benefits included increased access to medical knowledge, enhanced professional networking, and emotional support. However, challenges such as misinformation (44.1%), privacy concerns (55.5%), information overload (29.5%), and risks of personal data disclosure (31.3%) were identified as major concerns. Conclusion: The study highlights the significant impact of social media in nursing, providing an essential tool for professional development and patient engagement. However, risks such as misinformation and ethical concerns necessitate guidelines to ensure responsible usage. It is recommended that healthcare institutions implement policies to promote digital literacy and safeguard privacy while maximizing the benefits of social media in nursing practice.